ANALISA DISKRIMINASI RASIAL PADA INDUSTRI SEPAK BOLA INGGRIS - Nugraha, M. Fajar; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Racial discrimination is a long-standing issue plaguing the English football industry. Various prevention efforts and enforcement measures have been implemented by football federations, clubs, and the government. This phenomenon encompasses various forms of discriminatory behavior, from racial taunts in stadiums to hate speech spread on social media. This study aims to analyze the patterns, causes, and impacts of racial discrimination on players, coaches, and the dynamics of English football competitions. Using a qualitative approach with descriptive analysis, data was collected through literature reviews, federation annual reports, and documentation. The results show that racial discrimination in English football is influenced by historical factors, fan culture, and media use. The resulting impact not only affects the mental health and performance of players but also damages the image of English football and, indeed, England as a nation. Keywords: Culture, Football, Racial Discrimination, Social Issues